Mapping the Nexus of Transitional Justice and Peacebuilding. Issue 3 (2nd July 2016) - Baker, Catherine; Obradovic-Wochnik, Jelena
ABSTRACT: This article explores the convergences and divergence between transitional justice and peacebuilding, by considering some of the recent developments in scholarship and practice. It examines the notion of 'peace' in transitional justice and the idea of 'justice' in peacebuilding. It highlights that transitional justice and peacebuilding often engage with similar or related ideas, though the scholarship in each field has developed largely in parallel to each other, and often without any significant engagement between the fields of inquiry. The article also notes that both fields share other commonalities, insofar as they often neglect questions of capital (political, social, economic) and at times, gender. It is suggested that trying to locate the nexus in the first place draws attention to where peace and justice have actually got to be produced in order for there not to be conflict and violence. This in turn demonstrates that locally, 'peace' and 'justice' do not always look like the 'peace' and 'justice' drawn up by international donors and peacebuilders; and, despite the 'turn to the local' in international relations, it is surprising just how many local and everyday dynamics are (dis)missed as sources of peace and justice, or potential avenues of addressing the past.